Digital Literacy Socialization In Filtering Information And Utilizing Artificial Intelligence (Ai) Technology To Support Student Learning - En Tay; Feri Alpiyasin; Adzra Maisa Fayyadh; Aulia Rahmi Nur Fajriyah; Aulya Putri Syaharani; Azkia Muhammad Hanif; Belly Embun Pradana; Muhammad Ilham; Najja Rissalah; Nida Mutmainah; Rochyiat Ramdani; Tegar Dinar Harsya Ibrahim (LPPM STMIK Mardira Indonesia, 2024)
The community service initiative undertaken by the faculty and students of STMIK Mardira Indonesia seeks to confront the challenges presented by the swift dissemination of information in the digital age, including the widespread occurrence of hoaxes and phishing, while also harnessing the potential of Artificial Intelligence (AI) in education. The intended audience for this outreach comprises the parents of kindergarten pupils. This effort aims to enhance parents' digital literacy, enabling them to distinguish between accurate and deceptive information and to effectively utilize AI technology to support their children's educational development. The methodology employs a participatory instructional approach, integrating interactive presentations, conversations, and straightforward case studies or simulations. The anticipated results encompass enhanced parental comprehension of digital literacy, heightened capacity to discern misinformation, foundational knowledge of AI concepts and their educational applications, and practical advice on the secure and ethical use of AI in children's learning. This effort aims to foster a healthy and constructive digital environment within families, enabling parents to serve as effective mentors for their children in the digital age.